The somatic type of male and female pupils who play selected musical instruments - Mateusz Apanowicz (Kazimierz Wielki University, 2018)
Introduction. The changes in the physique and posture are affected not only by genome, but also by the epigenetic factor. Material and methods. 393 students from randomly selected music schools were qualified for the study. The measurement of body weight and height was conducted using a medical electronic scale. Conclusions 1.The slender type was most common among male and female pupils involved in the study. The medium and stout types were less popular but more common among boys. 2. The slender type was usually characteristic for female players of the grand piano, accordion and Western concert flute, the medium type for male guitar and violin players, whereas the stout one for male players of the grand piano.